Directive Vision Transformations in Iraqi Political Theatre: محمد عبدالرضا حسين-سهى طه سالم (Al-Academy, 2020)
The creative arts in general and the theatre in specific represent man's rushing and carving for freedom, goodness and beauty, and the relation between creativity and freedom has always been fluctuating following the censorship pressures of all types and shapes the political, religious and social. Since the theatre is the closest and more touching creative art to the problems of the society of numerous types and levels and it was and has always been playing an enlightening role in shedding light on what the societies experiencing with crises and problems in all directions. The theatre, thus, derives the essence of existence from life, through topics concerned with what the human being is. It seeks to be the real witness and partner in getting man rid of problems and everyday worries. This relation may be subject to treatments in many arts, but it manifested itself in the formation of the real image in the theatrical art. Therefore, the two researchers find it necessary to search and reveal the mechanisms of the directive vision and the method of its transformations by some theatre directors, who added creative and aesthetic concepts to their theatrical shows through the concepts of transformations and the directive vision.